(NmINERALXNOE SYRXE W \KONOMIKE RAZWIWA@]IHSQ STRAN (B/s - (NkOFANOW(B, (NiWAN tIHONOWI^s; (NiN(B-(NT MIROWOJ \KONOMIKI I MEVDUNARODNYH OTNO[ENIJ an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B. (NS(B. 158-163 (173 (NNAZW(B.)s
Keywords: (NmINERALXNOE SYRXE (B- (NrAZWIWA@]IESQ STRANYs